Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Facile synthesis of nanocomposites of CNF-Sn and C-Sn microspheres: Prospective field emitter - Badadhe, Satish S.; Yadav, Poonam; Suryawanshi, Sachin; More, Mahendra A. (Journal of Alloys and Compounds, 2022)
We report synthesis of Carbon nanofibers (CNFs) and hybrid nanocomposites namely, CNF-Sn and C-Sn microspheres using simple electrospinning technique, followed by annealing in controlled atmosphere. The as-prepared materials were characterized using X-raydiffraction (XRD), Field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Ultra-violet photoelectron spectroscopy (UPS), and Raman spectroscopy to reveal their physico-chemical properties. As carbon family members are potential materials for field emission (FE) based applications, owing to their high aspect ratio FE characteristics of the synthesized materials were explored at base pressure of 1 x 10(-8) mbar. Interestingly, the hybrid nanocomposite CNF-Sn and C-Sn emitters showed improved FE behavior (with the turn-on field of 3.4 and 1.36 V/mu m, respectively) in contrast to the pristine CNFs emitter (turn-on field of 5.4 V/mu m). Furthermore, the maximum emission current density is substantially enhanced, 7.75 and 4.6 mA/cm(2) for CNF-Sn and C-Sn emitters, respectively. The improvement in the FE behavior of nanocomposite emitters is attributed to the combined effect of morphology and modulation of electronic properties at the interface of nanocomposites. The results confirm that FE characteristics of pristine nanostructures can be greatly improved upon formation of their nanocomposites and this approach can be extended to other nanostructures for improving their multi-functionalities. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: carbon nanofiber; electrospinning; field emission; Nanocomposite; Tin